Le surréalisme central et les surréalismes périphériques : Roumanie, Québec, Grèce - Jacques Bouchard (Cahiers Balkaniques, 2017)
Surrealism, as imagined by André Breton, was in French: Breton detested foreign languages. For this reason the movement only extended into neighbouring European countries and the Surrealists who wrote in French were quickly recognized. Breton recognized also many Romanians and some Quebecers for linguistic reasons. The Greek Surrealists, even though they all spoke French, were long to be recognized, since their works – with one exception – were written in Greek.